UPAYA MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DI KELAS IV SD NEGERI 3 ARCAWINANGUN - Monica Bella Anggelia; Pratik Hari Yuwono; Yudha Febrianta; Dedy Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low scores in formative assessments in the subject of Pancasila Education. Only 51.28% of students achieved the Minimum Mastery Criteria (MMC), while 48.71% did not. Additionally, the teacher still applied conventional teaching methods, primarily using lectures. This research focuses on implementing the cooperative learning model of Teams Games Tournament (TGT) in the subject of Pancasila Education, particularly on the topic of “Cooperation in My Environment.” The aim of this study is to improve the learning achievement of Grade IV students at SD Negeri 3 Arcawinangun through the application of the TGT cooperative learning model. This study employed a classroom action research (CAR) method, conducted in two cycles, with each cycle consisting of two meetings. Data collection techniques included tests, observation, documentation, and questionnaires, with tools such as observation sheets, questionnaire sheets, evaluation test sheets, and documentation.The results showed a significant improvement in student achievement. Student learning activity observations increased from 64.1% in Cycle I, Meeting 1 to 72.56% in Meeting 2. In Cycle II, learning activity further increased to 77.17% in Meeting 1 and 84.32% in Meeting 2. Based on these improvements, it can be concluded that the application of classroom action research using the TGT cooperative model can enhance students' learning achievement in Pancasila Education for Grade IV students at SD Negeri 3 Arcawinangun.